ASPEK MORFOLOGI TERHADAP SEBARAN AWAN PANAS GUNUNGAPI MERAPI KABUPATEN SLEMAN DAERAH ISTIMEWA YOGYAKARTA Kasus: DAS Code - , HENKY NUGRAHA, Dr. Widiyanto, MS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Merapi volcano is the most active volcano in Indonesia. Pyroclastic flow as one of hazard in Merapi Volcano has caused many casualties and losses such as property, infrastructure, economic activities and the deaths of flora and fauna. Volcanic morphology has an important role related to pyroclastic flow distribution. The aims of this research are to